The Impact of System and Information Quality on User Satisfaction and Continuance Intention: An Analysis of Online Motorcycle Taxi (Ojek-Online) Applications - Novita Mariana; Isworo Nugroho; Saefurrohman Saefurrohman; Agus Prasetyo Utomo (Universitas Negeri Semarang, 2023)
Purpose: The study’s goal was to analyze the adoption of online motorcycle taxi (in Indonesia it is called an ojek online) technology with the purpose to keep using the application.Methods: The study used the System Success Model to develop this research model. It was conducted based on the premise that information quality and system quality positively influence the ease and usefulness of the system application. The ease and usefulness of the system application have implications for user satisfaction and the intention to continue using the system. The study employed Structural Equation Modeling (SEM) using PLS (SEM) 4.0 to test and evaluate the measurement model and structural model. A sample of 235 respondents who are users of the online motorcycle taxi system in Semarang City was used in the study.Result: Out of 10 hypotheses tested, 9 hypotheses were accepted and 1 hypothesis was rejected. The usefulness of the system had a negative and insignificant influence on the intention to continue using the system. The intention to continue using the online motorcycle taxi application was strongly determined by the ease of the application system and user satisfaction. The discoveredings also showed that the quality of the system had the strongest influence on the ease of the system. Novelty: This study was unique in combining the Technology Acceptance Model and Mclean Delone approach to test the quality of the online motorcycle taxi application towards user satisfaction and intention to continue using the application.